(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aimed to identify impact of a business risk-based audit approach on improving the quality of internal audit in public shareholding companies listed on the Palestine Stock Exchange. The data of the study was analyzed through the use of some statistical methods. The study concluded that there is an impact of the audit approach based on business risks in its dimensions, external category risks, operational risks and information risks on the quality of internal audit. The study recommended working on raising the level of coordination between the departments of risk management and internal auditing, paying attention to developing the capabilities and skills of internal auditors and enhancing the independence of the internal auditor, so that s/he can perform the tasks efficiently and effectively.